New amine adducts with carbon dioxide as blowing agents in the production of integral polyurethane foams - Szczepkowski, Leonard; Ryszkowska, Joanna; Auguścik-Królikowska, Monika; Leszczyńska, Milena; Przekurat, Sylwia; Przekurat, Adam (Polimery, 2020)
Blowing agents play an important role in the production of cellular polyurethanes. The traditional chemical blowing agent H2O/CO2 did not meet all application requirements. This led to the introduction of physical foaming agents in the 1950–1960s, which were subject to four further modifications due to climatic hazards. The recently introduced new generation of hydrofluoroolefins (HFOs) hydrocarbons is currently in the application assessment and meets the utility and climate requirements for now. Without waiting for a long-term final assessment of this blowing agent group, an attempt was made to introduce carbon dioxide in the form of adducts with aliphatic amines into the foaming process. As example compounds, CO2 adducts with aliphatic hydrocarbons containing also primary, secondary and tertiary nitrogen atoms in the same molecule were used. The synthesis of adducts was carried out by the absorption of carbon dioxide gas in a solution of amines in monoethylene glycol (MEG) and triethanolamine (TELA). The resulting solutions containing 12–16 wt % CO2 were next used in the application-oriented study. Amines regulating the foaming and gelation processes were used for the production of adducts, which allowed the elimination of organometallic gelling additives. Selected adducts were checked during the production of furniture chair seats on an industrial scale, obtaining integral foams in the range of density 190–294 kg/m3 and hardness 22–38 °ShA. In the production process of these foams carried out at PLASTPUR a double-stream foaming machine from Hennecke was used.